Tinciones para determinación de sustancia amiloidea y carbohidratos en tejidos humanos - Rodriguez Yumi, Geomara Lisseth, Sánchez Satán, Esthefanny Dayana (2023)
ABSTRACT: Abnormal accumulations of amyloid substance or carbohydrates in human tissue are the basis for the development of lethal diseases if not diagnosed in time. The objective of this present investigation was to specify the various stains used for the determination of amyloid substance and carbohydrates in human tissues. The methodology was based on a descriptive study, documentary and non-experimental design, cross-sectional and retrospective. The sample consisted of 59 scientific articles, selected by exclusion and inclusion criteria. Researched in university repositories, digital books, databases such as PubMed, Scielo, Medigraphic, Dialnet, Lilacs, Redalyc, Elsevier, Science Direct and SOLCA of the last 10 years. Through the analysis and discussion of the results it was concluded that histochemistry is the most used technique in the diagnosis of extracellular elements, based on the chemical change of tissue molecules to be stained with the intention of recognizing and studying specific structures. Congo Red has affinity for amyloid substance, 96.96% of the authors used this stain for its birefringent property that differentiates it from collagen and elastic fibers, considering Highman as the outstanding method, Meanwhile, for the detection of carbohydrates PAS led with 57.69%, followed by Alcian blue with 23.08% for its capacity to differentiate neutral mucins from acid mucins, PAS-AB with 7.69%, and with 3.84% for Azure A, toluidine blue and GomoriGrocott, respectively. For greater reliability some authors used contrast stains that allow visualization of structures other than those studied.